Rapid visualization of Clostridioides difficile toxins A and B by multiplex RPA combined with CRISPR-Cas12a - Jiang, Tong; Hu, Xinyi; Lin, Chunhui; Xia, Zhaoxin; Yang, Wensu; Zhu, Yi; Xu, Huaming; Tang, Hao; Shen, Jilu (Frontiers in Microbiology, 2023)
Purpose Clostridioides difficile (C. difficile) infection is the most common cause of nosocomial infection, which is a severe challenge in modern medical care. Currently, many laboratory diagnostic methods for C. difficile are available, such as PCR, culture-based tests, and antigen-based tests. However, these methods are not suitable for rapid point-of-care testing (POCT). Therefore, it is of great significance to develop a rapid, sensitive, and cost-effective method to detect C. difficile toxin genes. Methods Recently, the development of clustered regularly interspaced short palindromic repeats (CRISPR) technology has emerged as a promising tool for rapid POCT. In this study, we developed a rapid and specific detection platform for dual C. difficile toxins by combining recombinase polymerase amplification (RPA) and CRISPR/Cas12a. Results The platform includes multiplex RPA-cas12a-fluorescence assay and multiplex RPA-cas12a-LFS (Lateral flow strip) assay, through which the detection limit for tcdA and tcdB was 10 copies/μL and 1 copy/μL, respectively. The results can be more clearly distinguished using a violet flashlight, which realized a portable visual readout. The platform can be tested within 50 min. Furthermore, our method did not cross-react with other pathogens that cause intestinal diarrhea. The results of 10 clinical samples using our method was 100% consistent with those from real-time PCR detection. Conclusion In conclusion, the CRISPR-based double toxin gene detection platform for C. difficile is an effective, specific, and sensitive detection method, which can be used as a powerful on-site detection tool for POCT in the future.